Advanced glaucoma secondary to bilateral idiopathic dilated episcleral veins – a case report - Xin Rong; Mei Li (BMC Ophthalmology, 2018)
Abstract Background Idiopathic elevated episcleral venous pressure (IEEVP) or idiopathic dilated episcleral veins (IDEV) is a rare abnormality, and thus therapeutic treatment for this condition rarely is discussed. We report a case of a patient with bilateral glaucoma secondary to IDEV for whom intraocular pressures (IOPs) were controlled successfully by trabeculectomy. Case presentation A 50 year-old female with a complaint of persistent red eyes for over 30 years, presented with numerous tortuous and engorged episcleral vessels in both eyes (OU), open angles OU with spontaneous blood in Schlemm’s canal 360 degrees bilaterally. Orbital color Doppler examination showed the superior ophthalmic veins to be of normal calibre, with no reversal of flow. Head MRI with contrast and cerebral angiography were negative for arteriovenous fistula. Coronary angiography, color Doppler echocardiography and chest radiographs were within normal limits. A diagnosis of secondary glaucoma and IDEV was made. Neither anti-glaucoma medications, nor laser trabeculoplasty reduced the patent’s IOP effectively. Only after trabeculectomy was performed in each eye, were IOPs successfully controlled. Conclusions This case serves to remind clinicians of the importance of identifying and evaluating thoroughly patients with episcleral vessel dilation in non-inflamed eyes with no known cause. A misdiagnosis or missed diagnosis of long-term elevated intraocular pressure may result in significant damage to the optic nerve. In addition, when performing filtration surgery it is crucial that the ophthalmologist control the IOP and make an effort to prevent choroidal effusion.